Fortifikasi Tepung Daun Pepaya pada Pakan untuk Stimulasi Pertumbuhan Ikan Nila (Oreochromis niloticus) - Yusdalifa Ekayanti Yunus,; Ummu Kaltsum SC,; Fauzia Nur,; Sahabuddin,; Fitri Indah Yani,; Nurul Mutmainnah,; Rismawaty Rusdi, (Journal Galung Tropika, 2024)
One of the fundamental problems in tilapia aquaculture is the decline in water quality in the hatchery. The seed stage is more vulnerable to environmental changes that can reduce the gowth process of seeds and will further cause death. This study aims to determine the effect of fortification of papaya leaf flour (Carica papaya L.) to stimulate tilapia gowth. This study used an experimental method to treat different doses of papaya leaf flour mixed into the feed, namely 0%, 2%, 4%, and 6%, with the test animals used as tilapia seeds measuring 1.4 gams with a length of 3.2 cm. The proximate test results showed that the moisture, ash, crude fat, crude protein, crude fiber, and BETN content were suitable for tilapia fish needs. After 30 days of rearing with the test feed, there was an effect on the specific gowth rate parameters on day 15 and day 30 and the average absolute gowth. The best specific gowth rate (SG) at a dose of 2% was obtained at 6.606% on day 15 and 4.400% on day 30. The best average absolute gowth was obtained at 2% dose feeding with tilapia weight of 6.606 gams and length of 4.400 cm.